Dimensions and morphology of the sinus tympani: an anatomical study - Kumar, B. Y. Praveen; Venugopal, Deekshita; Parashuram, Rajapur; Veenapani, M. K.; Subhash, C.; Sunil, K. C.; Pardikar, Spandana S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The sinus tympani is a deep pocket of varying dimensions and shape situated in the retrotympanum. The sinus tympani lies medial to the facial nerve. Hence surgical access is difficult. This area is frequently involved in chronic otitis media attico antral type. Removal of disease from this area is difficult leading to cholesteatoma recidivism. The anatomy has been well described in literature. Its dimensions and morphology has not been described in the Indian population. Knowledge of the endoscopic anatomy of this area will help to eradicate disease leading to better results. Methods: A canal wall down mastoidectomy was performed on twenty wet temporal bones. A zero degree endoscope was introduced into the middle ear to view the sinus tympani. Using a graduated millimetre scale. The dimensions and morphology of the sinus tympani was studied. Results: Twenty wet bones were dissected. The mean height of the sinus tympani was 3.55 mm. The mean width was 2.22 mm and mean depth was 1.72 mm. The morphology was as follows: 13 bones had a type A morphology (classical type), 6 had a type B morphology (confluent), 1 bone had a type D morphology (restricted type). We did not encounter a type C sinus tympani in our study. Conclusions: The morphology and dimensions of the sinus tympani are variable. The otologist must have a complete knowledge of the anatomy of this area to successfully eradicate disease from this area.